Analysis of Traffic Accidents on the Lonjengan-Tanjam Section, Menjalin District, Landak Regency - Inong, Paramitha; Kadarini, S. Nurlaily; Said, Said (Fakultas Teknik Universitas Tanjungpura, 2025)
The rapid growth of the population has led to an increase in motor vehicle volume, which contributes to a higher risk of traffic accidents and results in significant social and economic impacts. Therefore, a comprehensive analysis is required to identify accident-prone areas and formulate effective mitigation strategies. This study was conducted along the Jalan Lonjengan